A Conceptual Framework of Academic Well-Being - Lianah The; Hannes Widjaya; Arnold Surya Nugroho; Frisca Desma Ayu Kusuma Wardani (Universitas Muhammadiyah Enrekang, 2024)
The organisational transformation in higher education institutions has troubled academics well-being, mostly where there is insufficient care and support from leaders to simplify the change. The study aims to establish the conceptual framework of academic well-being in Buddhist Colleges in Indonesia. Qualitative results designate that stress and conflict as significant consequences of organizational change; with other adverse effects including reduced academic freedom, family life, health, and distracted career prospects. As a result, reduction in academic satisfaction and well-being has occured. However, these contrary consequences were happened in a short term only. In addition, the idea of diminishing marginal suggests that academics resisted to change firstly but then believed the changes will create a better circumstance at a certain period. The conceptual framework is to help building academic well-being concepts in Buddhist College in Indonesia.Organizational Change, Academic Well-Being, Conflict, Academic Satisfaction